West Java Millenial Farmers Potential in Boosting the National Economy through the Export of Plantation Products - Mulyati, Yuyun; Setyawati, Iin Endah; Suganda, Dudung Ahmad (Budapest International Research and Critics University, 2022)
West Java millennial farmers have contributed Rp. 163.335.866.450 (5.89%) of the total exports of Rp. 2.768.897.950.950 in boosting the national economy through the export of coffee plantation products, coconut and their derivatives as well as palm sugar. With current technological developments, the millennial generation can be adaptive to technological developments to be implemented in the agricultural sector, so that the potential of West Java millennial farmers can be developed through technical guidance on cultivation, harvesting, post-harvest and marketing of plantation products by utilizing digital information technology. In the implementation of the millennial farmer program in West Java, it should be preceded by more intensive socialization by the implementing team and other stakeholders so that it is understood and supported by various levels of society so that its implementation is efficient in the use of resources that are factors of production and more effectively achieves the target of increasing income, so that Millennial farmers stay in the countryside, urban fortunes, and global businesses.